Thermal storage integrated into air-source heat pumps to leverage building electrification: A systematic literature review. (October 2022) - Ermel, Conrado; Bianchi, Marcus V.A.; Cardoso, Ana Paula; Schneider, Paulo S.
Abstract: Air-source heat pumps (ASHPs) can support a decarbonized economy by replacing combustion appliances in homes and electrifying heating systems in buildings. However, ASHPs have not seen significant adoption primarily due to deteriorated performance under cold conditions—at very low temperatures they require auxiliary resistance heating to meet the heating demand and defrost the evaporator. The additional heat lowers the system efficiency. Thermal energy storage (TES) is a candidate technology to help overcome some of these issues. This paper presents a systematic literature review to map the existing research on the integration of TES into ASHPs. Our review of 59 publications indicates that thermal storage increases the ASHP coefficient of performance by 27% on average, albeit with higher initial cost compared to conventional fossil-fueled heating systems. Phase change materials may be ideal to be integrated with ASHPs due to their high energy density and compact design, but only a few publications address TES sizing and design. First and Second Laws of Thermodynamics are widely used to create metrics to assess ASHP-TES integration, and only recently have cost and environmental impact been explored. This literature review suggests that more comprehensive metrics are needed to evaluate the potential benefits of ASHP-TES systems. Highlights: In ASHP-TES systems the most common configuration is TES operating as a buffer TES was also applied in heat exchangers, waste heat, and hybrid solar systems Defrosting was addressed in 37% of the papers included in the SLR Latent materials appeared in 63% of the reviewed works Only recently metrics like C O 2 emission and costs have been employed in ASHP-TES